2017
DOI: 10.1037/adb0000267
|View full text |Cite
|
Sign up to set email alerts
|

Substance use prevention and treatment outcomes for emerging adults in non-college settings: A meta-analysis.

Abstract: Emerging adults have the highest prevalence rate of alcohol and drug use and represent a large proportion of treatment admissions in the United States. Those who do not attend college experience higher rates of use and may not have similar advantages as those attending college. A systematic review included studies investigating prevention and treatment outcomes among emerging adults in non-college settings. We included studies reporting an average age between 18 and 25 conducted outside of college settings. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 49 publications
2
32
0
2
Order By: Relevance
“…The extant literature argues that developmental context indeed differs between college and non-college young adults, but heterogeneity also exists within these groups (Arnett & Tanner, 2011). From an intervention standpoint, a recent meta-analysis examined 18 clinical trials with non-college or mixed college and noncollege samples, and reported a small but statistically significant effect size in contrast to minimal or no treatment (Davis, Smith, & Briley, 2017). While the close to 20 studies targeting this population is a somewhat heartening number, substance use outcomes and modalities of intervention were variable in the sample.…”
Section: Non-college Young Adultsmentioning
confidence: 99%
“…The extant literature argues that developmental context indeed differs between college and non-college young adults, but heterogeneity also exists within these groups (Arnett & Tanner, 2011). From an intervention standpoint, a recent meta-analysis examined 18 clinical trials with non-college or mixed college and noncollege samples, and reported a small but statistically significant effect size in contrast to minimal or no treatment (Davis, Smith, & Briley, 2017). While the close to 20 studies targeting this population is a somewhat heartening number, substance use outcomes and modalities of intervention were variable in the sample.…”
Section: Non-college Young Adultsmentioning
confidence: 99%
“…Existing studies in New York have focused on older beneficiaries [19] and young adults are an understudied population. [20, 21] Access to substance use disorder treatment services have been challenging, especially for young adults who prefer buprenorphine and naltrexone compared to methadone [22, 23], as limited access to buprenorphine providers have been an ongoing problem [24]. Age effects of the current epidemic have been understudied, especially research on MAT [25].…”
Section: Introductionmentioning
confidence: 99%
“…This research has important clinical implications. Many empirically supported evidencebased treatments (e.g., motivational interviewing) aimed at reducing alcohol and cannabis use in emerging adults have positive outcomes (Davis et al, 2017;Laporte et al, 2018;Stein et al, 2018). A review of the literature shows that interventions which incorporate aspects of mindfulness, such as mindfulness-based relapse prevention or mindfulness meditation, are effective in reducing alcohol and cannabis use in subclinical (de Dios et al, 2012;Vinci et al, 2014) and clinical populations (Bowen et al, 2014;Enkema & Bowen, 2017;von Hammerstein et al, 2019).…”
Section: Discussionmentioning
confidence: 99%